2008
DOI: 10.1002/anie.200803230
|View full text |Cite
|
Sign up to set email alerts
|

C1‐Symmetric Monosubstituted Chiral Diene Ligands in Asymmetric Rhodium‐Catalyzed 1,4‐Addition Reactions

Abstract: Asymmetric catalysis provides outstanding tools to introduce chiral information to a substrate by using only catalytic amounts of a chiral transition-metal complex.[1] The success of these efficient asymmetric processes relies on the development of chiral ligands that form a complex with the metal; until very recently phosphorus-, nitrogen-, and oxygen-containing chiral ligands were the only ones available. Recently, the groups of Hayashi and Carreira independently reported the use of chiral dienes in asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(39 citation statements)
references
References 54 publications
0
39
0
Order By: Relevance
“…Since the first application of chiral (S,S)-2,5-dibenzylbicyclo[2.2.1]heptadiene ((S,S)-L27b) in the addition of phenylboronic acid to cyclohex-2-enone by Hayashi and coworkers [93], a variety of bicyclic diene scaffolds [94][95][96][97][98][99][100][101][102][103][104] has been successfully applied (Scheme 1.15). Independently, Carriera and coworkers reported the application of a chiral diene for Ir-catalyzed allylic substitution [105].…”
Section: Diene Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first application of chiral (S,S)-2,5-dibenzylbicyclo[2.2.1]heptadiene ((S,S)-L27b) in the addition of phenylboronic acid to cyclohex-2-enone by Hayashi and coworkers [93], a variety of bicyclic diene scaffolds [94][95][96][97][98][99][100][101][102][103][104] has been successfully applied (Scheme 1.15). Independently, Carriera and coworkers reported the application of a chiral diene for Ir-catalyzed allylic substitution [105].…”
Section: Diene Ligandsmentioning
confidence: 99%
“…A systematic exploration of different bicyclic scaffolds for chiral diene, revealed that the 2,5-disubstituted bicyclo [ onto β-silyl α,β-unsaturated ketones [104]. Using the scaffold developed by Carreria (L30), it was found that just the mono-substitution of the bicyclo[2.2.2]octadiene framework with an aryl moiety (L29) was necessary to achieve high enantioselectivities [44,103]. In this first systematic investigation of the steric effects of mono-substituted chiral dienes, the ortho positions on the aromatic moiety (i.e., 2,6-Me 2 C 6 H 3 ) were found to be important to achieve highest selectivities.…”
Section: Diene Ligandsmentioning
confidence: 99%
“…[26] Perhaps the most common method for the generation of β -arylated amides is a transition metal-catalyzed conjugate addition of an arylmetallic species to an α , β -unsaturated amide (route b). [27] A rhodium-catalyzed addition of arylboronic acids to lactams provides the desired β -arylated products in yields and enantiomeric excess up to 99%. [27b] However, the rhodium-catalyzed addition of phenylboronic acid to an acyclic amide provided the desired product in only 40% yield with an enantiomeric ratio of 90:10.…”
Section: Resultsmentioning
confidence: 99%
“…128,129 However, the applications of bis-sulfoxide ligands in stereoselective synthesis have been largely overlooked. [130][131][132][133][134][135][136][137] In 2008, Dorta et al have disclosed that chiral bis-sulfoxides can be employed as ligands in stereoselective late-transition metal catalysis. Pre-catalyst [{(P,R,R)-p-tol-BINASO}RhCl] 2 L24 acts as a reactive showing excellent stereoselectivities in the 1,4-addition of different arylboronic acids 2 to cyclic, electron-poor compounds 1a-c,g,w.…”
Section: Methodsmentioning
confidence: 99%